Mental reality - Strawson, Galen (Representation and mind., 2010)
"In Mental reality, Galen Strawson argues that much contemporary philosophy of mind gives undue primacy of place to publicly observable phenomena, nonmental phenomena, and behavioral phenomena (understood as publicly observable phenomena) in its account of the nature of mind. It does so at the expense of the phenomena of conscious experience. Strawson describes an alternative position, "naturalized Cartesianism," which couples the materialist view that mind is entirely natural and wholly physical with a fully realist account of the nature of conscious experience. Naturalized Cartesianism is an adductive (as opposed to reductive) form of materialism. Adductive materialists don't claim that conscious experience is anything less than we ordinarily conceive it to be, in being wholly physical. They claim instead that the physical is something more than we ordinarily conceive it to be, given that many of the wholly physical goings on in the brain constitute--literally are--conscious experiences as we ordinarily conceive them. Since naturalized Cartesianism downgrades the place of reference to nonmental and publicly observable phenomena in an adequate account of mental phenomena, Strawson considers in detail the question of what part such reference still has to play. He argues that it is a mistake to think that all behavioral phenomena are publicly observable phenomena. This revised and expanded edition of Mental Reality includes a new appendix, which thoroughly revises the account of intentionality given in chapter 7"--MIT CogNet